Wrestling with God and with evil : philosophical reflections - Vroom, H. M., 1945- (Currents of Encounter, 2007)
The fact of evil continues to raises questions - questions about the relationship between God and evil but also questions about human involvement in it. At the beginning of the twenty-first century, it is now time to see the existence of evil not just as a problem for belief in God; it is a problem for belief in humanity itself as well. For human involvement in evil is not simply a matter of coping with evil but also concerns the fact that humans themselves often seem to do wrong and evil inevitably. Human finitude, ignorance and the unforeseeable consequences of good intentions as well as of neglect can often lead to tragedy. This volume contains contributions from an equal number of male and female scholars in Western Europe and America. It contains discussions of thinkers like Kant, Kierkegaard, Barth, Weil, Levinas, Naber, Caputo and Johnson. It deals with issues like tragedy, finitude, critiques of Western culture, violence and God, and the question of whether theodicies are needed or are even honest. This volume offers an interesting survey of 'wrestling with God and evil' from a variety of perspectives in the philosophy of religion on both sides of the Atlantic.